AODWE-006 Efficacy of ustekinumab for induction and maintenance of histological healing in patient's with crohn's disease. (17th June 2017) - Li, K; Chan, D; Pollack, P; Jacobstein, D; Brodmerkel, C; Gasink, C; Feagan, B; Sandborn, W; Rutgeerts, P; Hertogh, G De
Abstract : Introduction: Ustekinumab (UST) has been shown to induce and maintain clinical response and remission and to produce clinically meaningful endoscopic improvement in patients with moderate-severe Crohn's disease (CD). Effects of UST on histologic CD activity were evaluated in a substudy of the induction (UNITI-1 and 2) and maintenance (IM-UNITI) Phase 3 studies. Method: Biopsies were taken at induction baseline(I-Wk0), Wk8(I-Wk8), and maintenance Wk44(M-Wk44) from 3 sites (ileum, splenic flexure, rectum) and blindly scored by an expert GI pathologist (GDH) using the Global Histology Activity Score (GHAS 1 ). At I-Wk0, pts received a single IV dose (UST 130 mg, UST 6 mg/kg, or PBO). At I-Wk8, UST induction responders were re-randomised to subcutaneous (SC) PBO, UST 90 mg q12w or UST 90 mg q8w. Histology data from 251 substudy pts with simple endoscopic score for CD (SES-CD)≥3 at I-Wk0 were eligible for analysis. The relationship between GHAS and SES-CD was evaluated by Spearman correlation. Histologic improvements were assessed within groups (UST, PBO) and between groups (UST vs. PBO, at I-Wk0, I-Wk8 and M-Wk44). Results: Regional and overall GHAS were moderately correlated with SES-CD at all timepoints (r 0.6, p<0.001). GHAS was significantly reduced at I-Wk8 in pts treated with UST (from 10.4 to 7.1, p<0.001) but not PBO (from 9.2 to 7.8). At M-Wk44 in the randomised population, a continued reduction in GHAS from I-Wk8 was observed with UST 90 mg SC q8w (from 7.39 to 6.07, p=0.07) but not UST 90 mg SC q12w (from 5.29 to 8.67) or PBO (from 9.19 to 10.85). In the pooled maintenance population (randomised and non-randomised), continued histologic improvement from I-Wk8 was observed with UST 90 mg q8w (7.14 to 5.19, p<0.0001), but not UST 90 mg q12w (from 6.14 to 7.18) or PBO (from 8.19 to 8.85). Consistent results are observed in between-group (UST vs. PBO) analyses, numerically greater GHAS reduction was observed for UST. Conclusion: Histologic and endoscopic disease activities were moderately correlated. Consistent with previously reported results, statistically significant histologic improvements were observed in pts induced with UST, but not PBO. Trends for greater and continued histologic improvement were observed in pts who received UST 90 mg q8w maintenance. Disclosure of Interest: K Li Conflict with: Janssen R and D, D Chan Conflict with: Janssen R and D, P Pollack Conflict with: Janssen R and D, D Jacobstein Conflict with: Janssen R and D, C Brodmerkel Conflict with: Janssen R and D, C Gasink Conflict with: Janssen R and D, B Feagan: None Declared, W Sandborn: None Declared, P Rutgeerts: None Declared, G De Hertogh: None Declared